Unraveling Phylogenetic Relationships via A. carbonarius and A. tubingensis Sequence Analyses - Sabah Ben Fredj Melki; Ehi Sheena Omoregie; Ahmed Mliki (Biology and Life Sciences Forum, 2023)
The aspergilli comprise a diverse group of filamentous fungi spanning over 200 million years of evolution. In this work, we report a clarification of the phylogenetic relationship between A. carbonarius and A. tubingensis via the screening of ITS-5.8RDNA, (niiA-niaD), ß-tubulin, and eEF-1 genes. The phylogenetic analysis of aspergilli ITS-5.8rDNA sequences divided A. carbonarius and A. tubingensis into two coherent clusters and showed a close intergeneric relationship, which is in keeping with the existing morphological and taxonomic classification. Herein, A. carbonarius exhibits a complete similarity (100%) for the three target genes: intergenic region of (niiA-niaD), ß-tubulin, and eEF-1. The tree resulting from a bootstrap analysis indicates branch points when the significance is 98% minimum for each gene (ß-tubulin and eEF-1). The phylogenetic analysis of the aspergilli genome structure provided a quantitative evaluation of the forces driving long-term eukaryotic genome evolution. It also led to an experimentally validated model of mating-type locus evolution, suggesting the potential for sexual reproduction in A. carbonarius and A. tubingensis. This is the first work describing the evolutionary relationship between both species. Nevertheless, this discovery might be viewed as typical during the process of new taxonomic evolution.